Mathematics 2008 | Study Mode

Join Discuss Share to WhatsApp
Question 71
A
\(\frac{2}{3}\)
B
-\(\frac{2}{3}\)
C
-\(\frac{3}{2}\)
D
\(\frac{4}{3}\)
Explanation
3x + 2y + 1 = 0

y = mx + c

2y = -3x - 1

y = -\(\frac{3}{2}\) x -\(\frac{1}{2}\)

m = -\(\frac{3}{2}\)

Correct option: C
Join Discuss Share to WhatsApp
Question 72
A
5
B
23
C
20
D
50
Explanation
L\(\begin{pmatrix} x_1 & y_1 \\ -1 & -6 \end{pmatrix}\) m L\(\begin{pmatrix} x_2 & y_2 \\ -3 & -5 \end{pmatrix}\)

D = \(\sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2}\)

D = \(\sqrt{(-3 - (-1)^2 + (-5 -(-6)^2}\)

D = \(\sqrt{(-3 + 1)^2 + (-5 + 6)^2}\)

D = \(\sqrt{(-2)^2 + 1^2}\)

D = \(\sqrt{4 + 1}\)

D = \(\sqrt{5}\)

Correct option: A
Join Discuss Share to WhatsApp
Question 73
A
\(\frac{3}{4}\)
B
\(\frac{3}{5}\)
C
\(\frac{2}{4}\)
D
\(\frac{1}{4}\)
Explanation
sin \(\theta\) = \(\frac{3}{5}\), find tan \(\theta\)

sin \(\theta\) = \(\frac{opp}{hyp}\) = \(\frac{3}{5}\)

52 = x2 + 32

25 = x2 + 9

x2 = 16

x = \(\sqrt{16}\)

x = 4

tan = \(\frac{3}{4}\)

Correct option: A
Join Discuss Share to WhatsApp
Question 74
A
184m
B
185m
C
186m
D
187m
Explanation
Tan 20o = \(\frac{68m}{x}\)

x tan 20o = 68

x = \(\frac{68}{tan 20}\) = \(\frac{68}{0.364}\)

x = 186.8

= 187m

Correct option: D
Join Discuss Share to WhatsApp
Question 75
A
(x2 - 1)
B
3x(x2 - 1)
C
3X2 - 1
D
7X6 - 5X4
Explanation
y = \(\frac{x^7 - x^5}{x^4}\) = \(\frac{x^7 - x^5}{x^4}\)

Y = X3 - X

\(\frac{dy}{dx}\) = 3x3 - 1 - x1 - 1

= 3x2 - xo


\(\frac{dy}{dx}\) = 3x2 - 1

Correct option: C
Join Discuss Share to WhatsApp
Question 76
A
x cos x
B
x sin x
C
-x cos x
D
-x sin x
Explanation
y = sin x - x cos x

let; U = -x

\(\frac{dy}{dx}\) = -1

V = cos x

\(\frac{dx}{dx}\) = -5x

-x (-sin x) + cos x (-1)

x sin x - cos x

\(\frac{dy}{dx}\) = x sin x + cos x - cos x

\(\frac{dy}{dx}\) = x sin x

Correct option: B
Join Discuss Share to WhatsApp
Question 77
A
-\(\frac{1}{4}\)
B
-\(\frac{1}{2}\)
C
\(\frac{1}{4}\)
D
\(\frac{1}{2}\)
Explanation
y = x(1 + x)

y = x + x2

\(\frac{dy}{dx}\) = 1 + 2x

at minimum \(\frac{dy}{dx}\) = 0

therefore, 1 + 2x = 0 \(\to\) 2x = -1

x = -\(\frac{1}{2}\)

Correct option: B
Join Discuss Share to WhatsApp
Question 78
A
16
B
13
C
12
D
11
Explanation
\(\int ^{2}_{1}\)(6x2 - 2x)dx

= [\(\frac{6x^3}{3} - \frac{2x^2}{2}\)]2

= [2x3 - x2]2

= (2(2)3 - 4 - 2 + 1

= 16 - 4 - 2 + 1

= 17 - 6

= 11

Correct option: D
Join Discuss Share to WhatsApp
Question 79
A
7
B
1
C
2
D
3
Explanation
\(\int ^{\frac{\pi}{2}}_{-\frac{\pi}{2}}\)cosx

\([sin x]^{\frac{\pi}{2}}_{\frac{\pi}{2}}\)

= sin\(\frac{\pi}{2}\)- (-sin \(\frac{\pi}{2}\))

= sin \(\frac{\pi}{2}\) + sin \(\frac{\pi}{2}\)

= 2 sin \(\frac{\pi}{2}\)

= 2 sin 1.5714

= 2(0.2704)

= 0.5

= 1

Correct option: B
Join Discuss Share to WhatsApp
Question 80
A
15o
B
30o
C
45o
D
60o
Explanation

Explanation not provided, please join discuss, your contributions are welcomed


Correct option: C

Try this quiz in in E-test/CBT Mode
switch to Mathematics 2008 in CBT Mode

Previous Page Next Page
Question Map
Quiz link
Share Mathematics 2008 with your audience
Share to WhatsApp CBT mode Study mode copy link
​​​Help keep QUIZZERWEB running! 
A donation makes a contribution towards the costs, the time and effort that's going on in building and improving this platform.